Efektivitas Pelimpahan Sebagian Kewenangan Bupati Kepada Camat dalam Meningkatkan Pelayanan Publik (Peraturan Bupati Nomor 18 Tahun 2010 Tentang Pelimpahan Kewenangan dari Bupati Kepada Camat): Studi pada Kecamatan Ciamis - R. Naning Sri Hadiyani; Apri Budianto (Jurnal Riset dan Inovasi Manajemen, 2023)
This research is motivated by the results of preliminary observations that the Delegation of the Regent's authority to the Sub-district Head has not been running optimally. The improvement of public services is still not optimal. Limited facilities/infrastructure in the sub-district. The number of employees in the sub-district is still limited. Not all SKPDs that delegate authority have technical instructions for the implementation of the delegation of authority by the sub-district. The method used is a qualitative descriptive research method. The sampling technique uses a purposive sample technique, thus the sample in this study was 5 people. The data collection technique uses a questionnaire. The results of the study obtained are as follows: The Effectiveness of the Delegation of Part of the Regent's Authority to the Sub-district Head in Improving Public Services (Regent Regulation Number 18 of 2010 Concerning the Delegation of Part of the Authority from the Regent to the Sub-district Head) has been implemented well, especially in the implementation of aspects of licensing, recommendations, coordination, coaching, supervision, facilitation, and implementation. The implementation of Public Services according to Regent Regulation Number 18 of 2010 concerning the Delegation of Part of the Authority from the Regent to the Sub-district Head has been implemented well, such as in terms of service procedures, service time, service costs, service products, service facilities and infrastructure, and the competence of service officers. The obstacles faced by the Sub-district Head in the effectiveness of the delegation of Part of the Regent's Authority to the Sub-district Head in improving public services in the Sub-district in Ciamis Regency are Limited budget; Lack of facilities and infrastructure to support public services; Lack of human resources; Many human resources do not yet have competence; Lack of public awareness to make permits; not all technical instructions have been made regarding the delegated authority; There are still requirements that must be completed at the Regency level, whether permits must be made immediately at the sub-district, so that it hinders the completion process and the completion time becomes long. Meanwhile, the results of observations show that the number of service providers is still very limited, where each officer has their own main duties and functions. Efforts made by the Sub-district Head to overcome obstacles in the implementation of the delegation of Part of the Regent's Authority to the Sub-district Head in improving public services in the sub-districts in Ciamis Regency, are to increase the budget; complete and improve facilities and infrastructure to support services to the community; propose additional human resources; improve human resource competency through coaching and training; increase public awareness to make permits through socialization; request clear technical instructions regarding the delegated authority; in the completion process and completion time are made easier by assigning district employees to carry out services in the sub-district.